A Community of Relations: Mukurtu Hubs and Spokes - Christen, Kimberly; Merrill, Alex; Wynne, Michael (D-Lib magazine, 2017)
Describes the history of Mukurtu, a grassroots project to manage, circulate, and narrate the Warumungu Aboriginal community's digital materials using their own cultural protocols, and of Mukurtu CMS, community driven software developed out of the project that addresses the ethical curation of, and access to, cultural heritage. Focuses on the current project 'Mukurtu hubs and spokes : a sustainable national platform for community archiving', which will create regional centres of support and training and update the software to a 3.0 release, with hubs that will contribute to the software updates and provide local training and support for community users. Source: National Library of New Zealand Te Puna Matauranga o Aotearoa, licensed by the Department of Internal Affairs for re-use under the Creative Commons Attribution 3.0 New Zealand Licence.